Comparison of the safety of remimazolam and propofol during general anesthesia in elderly patients: systematic review and meta-analysis - Liu, Xianchun; Zhang, Longyi; Zhao, Li; Zhou, Xuelei; Mao, Wei; Chen, Linlin; Zhu, Hongyu; Xie, Ying; Li, Linji (Frontiers in Medicine, 2025)
BackgroundRemimazolam is a novel sedative drug approved for procedural sedation and general anesthesia. Clinical trials have already explored its use in elderly patients for general anesthesia. For elderly patients with declining physical and physiological function, anesthesia safety is crucial. Most current clinical studies compare the safety of remimazolam and propofol, though the results are inconsistent. Therefore, we conducted a meta-analysis to compare the safety of remimazolam and propofol in general anesthesia for elderly patients.MethodsWe systematically searched the PubMed, Cochrane Library, Embase, and Web of Science databases for all published randomized controlled trials comparing remimazolam and propofol for general anesthesia in elderly patients. We synthesized data from eligible studies using relative risk or mean difference, and analyzed differences in hemodynamic stability and adverse effects between the two drugs. Data extraction and quality assessment were performed independently by two researchers.ResultsEight randomized controlled trials involving 571 participants were included. Compared to propofol, remimazolam was associated with a lower incidence of hypotension (RR = 0.51, 95% CI: [0.33, 0.81], I2 = 18%, p = 0.3 > 0.1) and bradycardia (RR = 0.56, 95% CI: [0.31, 1.02], Z = 1.88, p = 0.06 < 0.05). The mean arterial pressure after induction was higher in the remimazolam group (WMD = 3.95, 95% CI: [3.197, 9.498], Z = 3.95, p < 0.00001). The remimazolam group had a higher heart rate (HR) after induction compared to the propofol group (WMD = 7.89, 95% CI: [−2.39, 18.17], Z = 1.5, p = 0.13 > 0.05), but this result was not statistically significant. Among other secondary outcomes, the remimazolam group had lower incidences of injection site pain, nausea and vomiting, and hypoxemia compared to the propofol group, and also had a shorter extubation time.ConclusionIn this meta-analysis, compared to propofol, remimazolam reduced the incidence of hypotension, bradycardia, and injection site pain during general anesthesia in elderly patients. The mean arterial pressure (MAP) and heart rate (HR) were more stable after induction. Remimazolam may be a safer sedative for elderly patients.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024516950, CRD42024516950.